Crosstalk between fibroblasts and T cells in immune networks - Lee, Byunghyuk; Lee, Seung-Hyo; Shin, Kihyuk (Frontiers in Immunology, 2023)
Fibroblasts are primarily considered as cells that support organ structures and are currently receiving attention for their roles in regulating immune responses in health and disease. Fibroblasts are assigned distinct phenotypes and functions in different organs owing to their diverse origins and functions. Their roles in the immune system are multifaceted, ranging from supporting homeostasis to inducing or suppressing inflammatory responses of immune cells. As a major component of immune cells, T cells are responsible for adaptive immune responses and are involved in the exacerbation or alleviation of various inflammatory diseases. In this review, we discuss the mechanisms by which fibroblasts regulate immune responses by interacting with T cells in host health and diseases, as well as their potential as advanced therapeutic targets.